Modern Trends in the Development of Culture and Art Management - Kaxramonovna, Yusupaliyeva Dilafruz (Journal of Innovation in Education and Social Research, 2024)
This article describes the development of culture and art management, the role of management in the field of culture and art, and modern trends.